A Scoping Review of Life Design Intervention Research: Implications for Counselling and Psychotherapy Practice - Lewis, Bradley; Domene, José F. (Canadian Journal of Counselling and Psychotherapy, 2021)
The recently developed paradigm in career counselling known as life design has caused a proliferation of new interventions. A scoping study was performed to provide an overview of empirical support for the effectiveness of these interventions. Twelve articles that evaluate the efficacy of eight interventions were found. Interventions included individual and group forms of the Career Construction Interview and My Career Story. Others were group-based life design interventions, the Career Construction Genogram, an online-based life design intervention, and a classroom intervention designed for elementary children. Career adaptability was the most commonly evaluated outcome and participants were most commonly from Italy, with no study using North American participants. Experimental or quasi-experimental research designs were most frequently used, while several articles reported on case studies. The authors recommend that future research balance case studies and experimental designs and that further research should validate findings with Canadian populations. This article notes the synergistic potential of engaging with social constructionist approaches in the broader field of counselling and psychotherapy for developing new interventions.